The Impact of Fiscal Deficit and Nigeria’s Economic Development (International Journal of Scientific Research and Management (IJSRM), 2025)
This study descriptively appraised the impact of fiscal deficit and its implication on Nigeria’s economic development from 1990 to 2025. It was observed that Nigeria’s fiscal operations for about 37 years had resulted in deficit in 35 years and surpluses for only two years. Surprisingly, the increasing fiscal deficit had been skewed in favour of recurrent expenditure at the expense of capital expenditure. This pattern of deficit expenditure that is heavily recurrent in nature is not capable of driving economic development in the long run as advocated by economic theorists. Specifically, the study appraised fiscal deficit in relation to some identified indicators of development such as per capita income, economic growth (GDP), unemployment, inflation and Balance of payments (BOP). It was discovered that Nigeria’s fiscal deficit has contributed positively to the growth of per capita income, economic growth and stabilization of Balance of payments only. Fiscal deficit did not reduce unemployment and inflation rates within the period of study. Thus the study advocated for massive investment/expenditure on capital projects (such as infrastructure) as against recurrent projects. This is likely to have the efficacy of boosting output and reducing unemployment and inflation through the multiplier effect.